Potensi Alelopati Elstrak Metanol Daun Ketapang (Terminalia catappa L. ) Terhadap Perkecambahan Biji Gulma Putri Malu (Mimosa pudica L. ) - Masnur Turnip, Ayu Mahardhika, Riza Linda (Jurnal Protobiont, 2016)
The Ketapang leaf (Terminalia catappa) has allelochemical compounds which can inhibit the growth of other plants, so it has the potential to serve as a bioherbicide. This research aims to find out the concentration of the leaf extract of Ketapang (Terminalia catappa) that is capable of inhibiting the germination of Mimosa pudica seed. This research was carried out in the screen house of the Department of Biology, and the Chemistry Laboratory of the Faculty of Mathematics and Natural Sciences, Tanjungpura University Pontianak from May to June 2015. The research used a completely randomized design with five replications. The treatments consisted of control (K0), concentration of the extract of T.catappa at 10% (K1), 25% (K2), 50% (K3), and 75% (K4) respectively. The results showed that the extract of T.catappa at concentration of 50% (0.50 g/ml) was capable of inhibiting the germination of M.pudica weed seed up to 100%.